Gaya Hidup Beragama Komunitas Hijabers di Kota Padang - Elzi Wardani (Indonesian Journal of Religion and Society, 2019)
The veil for women in Indonesia seems to come across a new phase. Veil is no longer considered an ancient one, but a modernization to keep up with the times. The emergence of a variety of improper hijabers communities was a form of the high interest of veil. This study is aim to examine and explore the process of the community and the discovery between religion and lifestyle and the factor of the establishment of the community. This study conducted through qualitative with interviews as data collection techniques. Data analized through reduction, display, ferivication and interpretation. The result show; first, the factor in the formation of the hijabers community is religion broadcast, invited inspiring women and a place to share experiences. Second, the activities of the hijabers community are related to religion and moslem women livestyle, such as regular recitation, seminars, and sharing experiences. There are yearly activities that is is combination of all activities carried out by hijabers community. Third, the religious practices of the hijabers community are expression of their religious lifestyle in the public. In addition, it was also found that this community has a business mission with a hijab as a media.